A Methodology to Empirically Assess National and Farm-Specific Damages from Contamination of Grain Supply by a Genetically Engineered Strain. (August 2019) - Capps, Oral; Babula, Ronald A.
Abstract: On May 29, 2013, the U.S. government announced that contamination of non–genetically engineered wheat supplies occurred. We provide a methodology to empirically assess the impacts of this contamination event on national prices and on farm-specific prices and receipts for spring red hard wheat. Results suggest that U.S. spring red hard wheat farmers in the aggregate had lost receipts ranging from 32.77 million to 131.06 million and incurred a drop of 3.83% in wheat price equivalent to 0.27 per bushel. At the farm level, a hypothetical farmer received 0.31 less per bushel culminating in 4, 807 in lost receipts.